TINJAUAN HUKUM INTERNASIONAL TERHADAP PERLINDUNGAN SATWA DILINDUNGI DARI TINDAKAN EKSPLOITASI DAN PENGANIAYAAN DALAM PERTUNJUKAN SIRKUS DI INDONESIA BERDASARKAN CONVENTION ON INTERNATIONAL TRADE IN ENDANGERED SPECIES OF WILD FAUNA AND FLORA (CITES) - Mariana Gultom; Evi Deliana; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Utilization of animals as the object of circus recreation in Indonesia is still valid until today. Utilization is not just exploitation, but also animal abuse, which is done by animals such as animal circus animals, businesses that make it possible to find people. Circus performances of dolphins around the action of dolphins, called hazardous bears, honey bears, yellow-crested cockatoos and beavers. Bottled nose dolphins and sun bears are integral animals and are included in Appendix I CITES. If the items described above are not appropriate and in accordance with the article of the law. The Act does not seem to provide any benefit to the animals that the circus object is made of.The purpose of this study is to know the Protection of Animals from the Action of Exploitation and Torture in Circus Show in Indonesia based on the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) also To be known Implementation of Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) against the National Law.The animal circus performances have absolutely no educational value, but also circus performances also do not appreciate the life of animals, even more degrading the dignity of animals, also violate the rights and do not care about the welfare of animals. The circus that uses animals is more concerned with the entertainment aspect than the education aspect, especially the conservation and protection of the animals. Animals used in circus performances are protected animals that are included in Appendix I CITES such as bottlenose dolphins, tigers, elephants and bears who are endangered animals. This clearly violates the provisions of CITES and Law No. 5 of 1990 which discusses the conservation of Biological Resources as well as the Criminal Code. The CITES Convention has long been ratified but, it can not yet be implemented optimally to protect protected animals from threats of extinction. In this regard, a clear and specific national regulation should be established regarding the prohibition of the use of animals in circus rides and their protection with strict sanctions for perpetrators in the event of a violation. It may also consider ratifying an international convention that clearly regulates the prohibition of the use of animals to perform circus attractions in keeping with the existing national law. And against existing and applied rules to be applied clearly and decisively to perpetrators of violations.Keywords: Protection - Exploitation - Animals - CITES